Μελέτη και σχεδιασμός ηλιακού οχήματος - Αντρέου, Άντρια (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
The aim of this thesis is to design, with the help of design software, a vehicle that moves with the help of solar energy.The design of the vehicle was made in accordance with specific regulations required by a speed competition of solar cars.There have been performed several surveys and studies of various cases of the design and construction of solar cars in order to determine the appropriate shape and calculate the various other parameters of electronic equipment such as motors, batteries and a system that provides transmission of power.Also various types of solar panels and other necessary accessories have been studies.Subsequently, calculations, options and plans were made for the final form and shape of the solar car, followed by calculations and drawings for the various systems (transmission of power, brake system etc.) and for related accessories.
Keywords: Solar cars-Design; Solar cars-Construction; Ηλιακά αυυτοκίνητα-σχεδιασμός; Ηλιακά αυτοκίνητα-κατασκευή